Keragaan Anggrek Persilangan ♀ Vanda Celebica X ♂ Vanda Dearei Hasil Iradiasi Sinar Gamma - Sri Hartati; Ahmad Yunus; Fajar Nugroho (Agrotechnology Research Journal, 2017)
Variation on orchid is an advantage that allows plant as breeding material. Orchid in plant breeding has a target to increase plant genetic diversity character who favored by the consumer. Efforts to increase genetic diversity among others by artificial mutation using gamma ray irradiation. This research aims to study the influence of gamma ray irradiation dose against the performance of morphology and growth of crossbred orchids ♀Vanda celebica x ♂Vanda dearei. Research using completely randomized design single factor that is dose gamma ray irradiation 0 Gray, 10 Gray, 20 Gray, 30 Gray, 40 Gray and 50 Gray. Data were analyzed descriptively, compared plant irradiation treatments with control plants to determine the effect of irradiation on morphology and growth plant. The results showed dose irradiation treatment increased the diversity of plant height, leaf amount, leaf length, leaf color changes, the amount and length of roots. 10 Gray dose irradiation increases as height and length plant leave. 30 Gray dose irradiation increase in the number of leaves. Leaf color change occurs at 20 irradiation treatments Gray and 50 Gray.